Археологізовані сліди орних знарядь на території стародавнього Чернігова - Черненко, О.Є. (Археологія і давня історія України, 2021)
Стаття присвячена розгляду залишків оранки, виявлених під час археологічних досліджень
Чернігова (територія фортеці-дитинця та т. зв.
Окольного граду) у 1986, 2005—2006 і 2010 рр.;
обґрунтовується її датування часом не раніше
Х ст. та висловлюються припущення щодо типів
використаних орних знарядь. Evidence of ancient plowing systems known in
Scandinavia, Denmark, Italy and Poland was found in
North-western Rus on the Rurik hill-fort and Novgorod.
Almost always they were dated to the 9th—10th century.
Evidence of several arable area, dated by the ceramics of
Romny culture to the 9th—10th century, was occurred on
the left bank of the Dnieper: in Prorva, near Trubchevsk
(Bryansk region, Russian Federation) and Avtunichi in
the Chernihiv region. A ploughed area in the northern
part of the Chernihiv hill fort was recorded by V. Kovalenko
in 1986. Similar traces were recorded by the author
in 2005—2006 on the neighboring site at the area of
more than 1,500 m2. The plough line were visible in the
virgin soil as long (up to 10 m) rather narrow (from 2 to
10 cm) and deep (5—10 cm) furrows of triangular crosssection.
They were filled by the light grey sandy loam
with charcoal inclusions. The furrows overlapped each
other perpendicularly forming the dense mesh. Individual
double furrows with an internal distance of about 20
cm were also recorded. They are evidence of use of the
double plough with narrow sub-triangular points. Judging
by the location of the furrows the crosswise ploughing
of the field was repeatedly carried out over several
years. The horizon above ploughing was dated to the
10th century. This dating was based first of all on the
finds of rough thick-walled Rus ceramic vessels with a
slightly turned, flaring, flat rims, in combination with
single fragments of handmade Romny culture ceramics
and a slate spindle whorl. The presence of the plowing
system directly before the appearance of settlement also
challenges the frequently expressed opinion that earlier
layers of the of the Chernihiv hill fort were completely
destroyed by later activity. Had that been the case, the
furrows would not have survived either.